2019
DOI: 10.1111/1744-7917.12698
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles of juvenile hormone signaling during early oogenesis in Drosophila

Abstract: Juvenile hormone (JH) signaling plays crucial roles in insect metamorphosis and reproduction. Function of JH signaling in germline stem cells (GSCs) remains largely unknown. Here, we found that the number of GSCs significantly declined in the ovaries of Met, Gce and JHAMT mutants. Then we inhibited JH signaling in selected cell types of ovaries by expressing Met and Gce or Kr-h1 double-stranded RNAs (dsRNAs) using different Gal4 drivers. Blocking of JH signaling in muscle cells has no effect on GSC numbers. Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…A recent study reported that the female GSC numbers are regulated by another important class of insect hormones, namely the juvenile hormones (JHs) ( Luo et al, 2020 ). JHs are sesquiterpenoids synthesized in the corpora allata ( Jindra et al, 2013 ; Santos et al, 2019 ; Kurogi et al, 2021 ).…”
Section: Are Insulin-like Peptides and Juvenile Hormones In Drosophila Melanogaster Involved In Mating-induced Increasmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported that the female GSC numbers are regulated by another important class of insect hormones, namely the juvenile hormones (JHs) ( Luo et al, 2020 ). JHs are sesquiterpenoids synthesized in the corpora allata ( Jindra et al, 2013 ; Santos et al, 2019 ; Kurogi et al, 2021 ).…”
Section: Are Insulin-like Peptides and Juvenile Hormones In Drosophila Melanogaster Involved In Mating-induced Increasmentioning
confidence: 99%
“…JH binds to two JH receptors, Methoprene-tolerant (Met) and Germ cell-expressed bHLH-PAS (Gce) ( Jindra et al, 2013 ). Double knockdown of Met and Gce in cap cells and terminal filament cells reduces the number of female GSCs ( Luo et al, 2020 ). This also validated in animals where JH biosynthetic enzyme (JH acid O -methyltransferase) is knocked down ( Luo et al, 2020 ).…”
Section: Are Insulin-like Peptides and Juvenile Hormones In Drosophila Melanogaster Involved In Mating-induced Increasmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we favor a model in which expression of the key JH biosynthetic gene, jhamt and JH reporter activity within the mesoderm reflects local production and paracrine signaling ( Fig 1b,e ). Evidence for local JH activity in adult Drosophila intestines 50 and germline stem cell niches of adult Drosophila 51 has been described, with the caveat that many gonadal Gal4 drivers are also active in the nervous system 52 . Our data build on these recent findings and suggest that JH functions in a short range, paracrine manner, similar to the mammalian bioactive isoprene RA.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that JHA insecticides can affect the social activity of the honey bee and change its growth and development processes [25,26]. Genes such as cytochrome CYP6AS5 (CYP6AS5), chitinase (CHT1), cytochrome CYP15A1 (CYP15A1), and juvenile hormone acid methyltransferase (JHAMT) reportedly induce responses when insects are under JHA stress [27][28][29]. Currently, with the wider use of JHA insecticides in pest control, it is becoming increasingly important to test the toxicity of pyriproxyfen, fenoxycarb, and methoprene in honey bees as well as their regulation and molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%